Assessing the impact of biochar and nitrogen application on yield, water-nitrogen use efficiency and quality of intercropped maize and soybean - Wang, Lixue; Yu, Binhang; Ji, Jianmei; Khan, Ismail; Li, Guanlin; Rehman, Abdul; Liu, Dan; Li, Sheng (Frontiers in Plant Science, 2023)
Biochar (BC) and nitrogen (N) application have the potential to increase grain yield and resource use efficiency in intercropping systems. However, the effects of different levels of BC and N application in these systems remain unclear. To address this gap, a two-year (2021-2022) field experiment was conducted in Northeast China to assess the impact of BC (0, 15, and 30 t ha-1) and N application (135, 180, and 225 kg ha-1) on plant growth, yield, water use efficiency (WUE), and N recovery efficiency (NRE) in an intercropping system of maize and soybean. The results showed that combination of BC and N significantly affected the yield, WUE and NRE. The treatment of 15 t ha-1 BC and 180 kg ha-1 N increased grain yield and WUE, while the 15 t ha-1 BC and 135 kg ha-1 N treatment enhanced NRE in both years. However, BC did not enhance the protein and oil content in intercropped maize, especially in the first year, but increased maize starch content. The TOPSIS method revealed that the comprehensive assessment value first increased and then declined with increasing BC and N application. Overall, BC improved the performance of maize-soybean intercropping system in terms of yield, WUE, NRE, and quality while N fertilizer input was reduced. The highest grain yield in two years was achieved with BC of 17.1-23.0 t ha-1 and N of 156-213 kg ha-1 in 2021, and 12.0-18.8 t ha-1 BC and 161-202 kg ha-1 N in 2022. These findings provide a comprehensive understanding of the growth of maize-soybean intercropping system and its potential to enhance production in northeast China.